Patterns of long‐term vegetation change vary between different types of semi‐natural grasslands in Western and Central Europe. (18th March 2019) - Diekmann, Martin; Andres, Christian; Becker, Thomas; Bennie, Jonathan; Blüml, Volker; Bullock, James M.; Culmsee, Heike; Fanigliulo, Miriam; Hahn, Annett; Heinken, Thilo; Leuschner, Christoph; Luka, Stefanie; et al.
Abstract: Questions: Has plant species richness in semi‐natural grasslands changed over recent decades? Do the temporal trends of habitat specialists differ from those of habitat generalists? Has there been a homogenization of the grassland vegetation? Location: Different regions in Germany and the UK. Methods: We conducted a formal meta‐analysis of re‐survey vegetation studies of semi‐natural grasslands. In total, 23 data sets were compiled, spanning up to 75 years between the surveys, including 13 data sets from wet grasslands, six from dry grasslands and four from other grassland types. Edaphic conditions were assessed using mean Ellenberg indicator values for soil moisture, nitrogen and pH. Changes in species richness and environmental variables were evaluated using response ratios. Results: In most wet grasslands, total species richness declined over time, while habitat specialists almost completely vanished. The number of species losses increased with increasing time between the surveys and were associated with a strong decrease in soil moisture and higher soil nutrient contents. Wet grasslands in nature reserves showed no such changes or even opposite trends. In dry grasslands and other grassland types, total species richness did not consistently change, but the number or proportions of habitat specialists declined. There were also considerable changes in species composition, especially in wet grasslands that often have been converted into intensively managed, highly productive meadows or pastures. We did not find a general homogenization of the vegetation in any of the grassland types. Conclusions: The results document the widespread deterioration of semi‐natural grasslands, especially of those types that can easily be transformed to high production grasslands. The main causes for the loss of grassland specialists are changed management in combination with increased fertilization and nitrogen deposition. Dry grasslands are most resistant to change, but also show a long‐term trend towards an increase in more mesotrophic species. Abstract : Semi‐natural grasslands are famous for their high plant species diversity. In a meta‐analysis of 23 data sets from Germany and the UK we show that the total species richness in wet grasslands has declined over time, while in dry grasslands the number of species did not consistently change. However, there was a general decrease in the proportion of habitat specialists.